MEMBANGUN KINERJA KARYAWAN MELALUI ANALISIS LINGKUNGAN DAN BEBAN KERJA - Mrs Purwatiningsih (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
Inability to compete in the globalization is company failure in developing HR. Therefore, a study should be made factors that affect employee performance. This study aims to analyze the influence of work environment and workload on employee performance of PT Kesuma. The data collection technique of this research uses the questionnaire with a measurement scale of research variables such as the Likert scale for the Working Environment variable (X1), Workload (X2) and Performance (Y) as a form of respondent's approval level or disagreement to a series of questions that measure an object. The population of this research was based on all PT Kesuma personnel totaling 275 people. The sample used is based on the calculation of Slovin formula as many as 163 respondents (PT Kesuma personnel). The data analysis method uses validity and reliability test, classical assumption test, simultaneous test, partial test and determination test. The results of the study show that both partial and simultaneous, work environment and workload have a significant effect on performance. For optimal employee performance, PT Kesuma first builds a comfortable work environment